2011
DOI: 10.4061/2011/467906
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Treatment Practices in Elderly Women in a Community Hospital

Abstract: Background. Elderly women with breast cancer are considered underdiagnosed and undertreated, and this adversely affects their overall survival. Methods. A total of 393 female breast cancer patients aged 70 years and older, diagnosed within the years 1989–1999, were identified from the tumor registry of The Brooklyn Hospital Center. Comparisons between the 3 different subgroups 70–74, 75–79, and 80 years and older were made using the Pearson Chi Square test. Results. Lumpectomy was performed in 42% of all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Some authors found lower mastectomy rates in oBCP [2,5] whilst others found it increased [1,20,22,35] including larger epidemiological studies [36,37]. An informed consent has been shown to increase the compliance and patient satisfaction [38].…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…Some authors found lower mastectomy rates in oBCP [2,5] whilst others found it increased [1,20,22,35] including larger epidemiological studies [36,37]. An informed consent has been shown to increase the compliance and patient satisfaction [38].…”
Section: Surgical Treatmentmentioning
confidence: 96%
“…Surgery is still the cornerstone in the treatment of early-stage breast cancer. Several studies have shown that breast conservation surgery followed by radiation therapy is as effective as more extensive surgery options such as mastectomy [21]. Nevertheless, some studies suggest that elderly women are less likely to be offered breast conservation surgery than their younger counterparts [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Mammography for Breast cancer screening requested for 12.80 % of patients. Studies have shown that around 50% of patients with breast cancer are those older than 65 years of age and 35% are older than 70 years (33) . There are very few retrospective and prospective studies looking specifically at cancer screening in the elderly.…”
Section: Discussionmentioning
confidence: 99%